2012
DOI: 10.1182/blood-2011-07-368753
|View full text |Cite
|
Sign up to set email alerts
|

Rac signaling in osteoblastic cells is required for normal bone development but is dispensable for hematopoietic development

Abstract: IntroductionHematopoietic stem cells (HSCs) give rise to all lineages of mature blood cells and maintain hematopoiesis in vivo through a balance of self-renewal and differentiation. To maintain this balance, HSCs are supported within a complex milieu known as the hematopoietic microenvironment (HM) or HSC niche. 1,2 This HM includes cellular components (osteoblastic cells, 3,4 perivascular cells, 5 and sympathetic neurons 6 ), bone mineral matrix, 7 and ionic gradients. 8 Trabecular bone appears to be particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…27 Long-term HSC and committed progenitor cell analyses were as described. 28,29 Data were collected using a FACScanto or FACS LSR Fortessa (BD Bioscience) and analyzed using DIVA Version 5.0.1 (BD Bioscience) or FlowJo Version 6.3 (TreeStar) software. Engraftment is expressed as the proportion of donor cells within the lineage analyzed or within the total CD45 ϩ cell population.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…27 Long-term HSC and committed progenitor cell analyses were as described. 28,29 Data were collected using a FACScanto or FACS LSR Fortessa (BD Bioscience) and analyzed using DIVA Version 5.0.1 (BD Bioscience) or FlowJo Version 6.3 (TreeStar) software. Engraftment is expressed as the proportion of donor cells within the lineage analyzed or within the total CD45 ϩ cell population.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Recently, it has been demonstrated that inhibition of prenylation by bisphosphonates rather activates than inactivates the RHO family of small-GTPases including RAC, CDC42 and RHO [9]. Interestingly, osteoblast-restricted Rac1 deletion leads to defective bone acquisition in vivo and knockdown impairs growth and induces apoptosis in the osteoblast cell line OP9 [68]. These data suggest that GGPP increases interaction of RAC1 with cellular membranes, which results in reduced activated RAC1 leading to decreased proliferation and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of this study suggest that in addition to RAS, other members of small-GTPases must be involved in regulation of FAS promoter methylation as well. Differences in responses to ibandronate of the epithelial CCL-51 cells compared to the mesenchymal cells suggest involvement of RAC1, a gene that has been found important for osteoblastic proliferation, differentiation and apoptosis [68]. The use of specific inhibitors of small-GTPases will help to clarify the mechanism of the selective epigenetic activation of FAS and other epigenetic silenced tumor suppressor genes [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 activity is important for normal bone development as well as adhesion, proliferation, and differentiation of osteoblasts in addition to controlling osteoclast number [39, 40]. Therefore, loss of Dock7 , a modulator of Rac1 and Cdc42 [8, 9, 14, 41], may in fact be altering osteoblast and osteoclast differentiation and function.…”
Section: Discussionmentioning
confidence: 99%